Imaging crystallographic phases using time-of-flight neutron diffraction - Gutmann, M; Kockelmann, W; Chapon, L; Radaelli, P (2006)
Identification and imaging of crystallographic phases inside an object can be achieved by time-of-flight neutron diffraction, based on a correction formula that is usually used to account for a sample offset on a powder diffractometer. The procedure allows the distribution of crystallographic phases along the incident beam path through the thickness of the material to be reconstructed. Phase reconstruction is demonstrated on a benchmark object. © 2006 Elsevier B.V. All rights reserved.